Measurement of prompt charged-particle production in pp collisions at √s = 13 TeV - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Journal of high energy physics, 2022)
The differential cross-section of prompt inclusive production of long-lived charged particles in proton-proton collisions is measured using a data sample recorded by the LHCb experiment at a centre-of-mass energy of √s = 13 TeV. The data sample, collected with an unbiased trigger, corresponds to an integrated luminosity of 5.4 nb−1. The differential cross-section is measured as a function of transverse momentum and pseudorapidity in the ranges pT ∈ [80, 10 000) MeV/c and η ∈ [2.0, 4.8) and is determined separately for positively and negatively charged particles. The results are compared with predictions from various hadronic-interaction models.